Are Visceral Proteins Valid Markers for Nutritional Status in the Burn Intensive Care Unit?. Issue 3 (May 2015) - Shields, Beth A.; Pidcoke, Heather F.; Chung, Kevin K.; Wade, Charles E.; Martini, Wenjun Z.; Renz, Evan M.; Wolf, Steven E.
Abstract : The aim of this study was to determine whether visceral protein levels increase under positive nitrogen balance during times of decrease in acute-phase reactant levels in patients with burn injury. This was a post hoc analysis of a prospective, interventional study approved by the local institutional review board. A total of 10 subjects between the ages of 18 and 72 with ≥20% total body surface area burn were enrolled over a 14-month period. Data were collected for five subjects (average age of 28 ± 8 years and total body surface area burn of 69 ± 15%) who met the inclusion criteria. Changes in visceral protein levels were examined along with nitrogen balance and acute-phase reactants when the subjects were on enteral nutrition, and the proteins were not examined during times of acute kidney injury. Descriptive statistics were performed, and linear regression was used to analyze the association of visceral proteins and nitrogen balance during times that acute-phase reactant levels were decreasing. The subjects received an average of 3044 ± 1613 kcal/day (39 ± 20 kcal/kg), meeting 72% of caloric goals and achieving positive nitrogen balance during 68% of the 40 weekly measurements, with 174 ± 85 g of protein intake per day (2.2 ± 1.1 g/kg). There was a weak relationship between nitrogen balance and changes in visceral protein levels during times that the acute-phase reactant levels were decreasing ( P > .05). Visceral proteins were found to be poor markers of nutritional status. This study is unique because the subjects were able to achieve positive nitrogen balance despite severe burns.